2023
DOI: 10.3389/fpsyt.2023.1060770
|View full text |Cite
|
Sign up to set email alerts
|

Stress-related reduction of hippocampal subfield volumes in major depressive disorder: A 7-Tesla study

Abstract: BackgroundMajor depressive disorder (MDD) is a prevalent health problem with complex pathophysiology that is not clearly understood. Prior work has implicated the hippocampus in MDD, but how hippocampal subfields influence or are affected by MDD requires further characterization with high-resolution data. This will help ascertain the accuracy and reproducibility of previous subfield findings in depression as well as correlate subfield volumes with MDD symptom scores. The objective of this study was to assess v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…The study suggests an anatomical connectivity substrate for apathy in DBS, emphasizing the importance of considering the location of active contacts within the STN in relation to its subdivisions for understanding and potentially mitigating apathy in PD patients undergoing DBS[ 53 ]. A study aimed to explore volumetric differences in hippocampal subfields between patients with major depressive disorder (MDD), specifically treatment-resistant depression (TRD), and HCs using automatic segmentation of hippocampal subfields software with ultra-high-field 7T MRI[ 54 ]. The results revealed reduced right-hemisphere CA2/3 subfield volume in both MDD and TRD patients compared to HCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study suggests an anatomical connectivity substrate for apathy in DBS, emphasizing the importance of considering the location of active contacts within the STN in relation to its subdivisions for understanding and potentially mitigating apathy in PD patients undergoing DBS[ 53 ]. A study aimed to explore volumetric differences in hippocampal subfields between patients with major depressive disorder (MDD), specifically treatment-resistant depression (TRD), and HCs using automatic segmentation of hippocampal subfields software with ultra-high-field 7T MRI[ 54 ]. The results revealed reduced right-hemisphere CA2/3 subfield volume in both MDD and TRD patients compared to HCs.…”
Section: Discussionmentioning
confidence: 99%
“…The study highlights the potential of high-resolution MRI data and automated segmentation techniques to identify biomarkers for MDD and TRD, providing insights into the pathophysiology of depression and potential implications for treatment selection. However, the authors acknowledge the need for caution in interpreting these results due to the small sample size and low power, emphasizing the importance of further research in this area[ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…26,27 Another study investigated the differences of hippocampal subfield volumes using 7-Tesla MRI, and analyzed the association between life-stressor and hippocampal subfield volumes, found righthemisphere CA2/3 subfield volume reduced in MDD patients, and left CA1, left CA4/DG, right subiculum total, left hippocampus total, and right hippocampus total were negatively associated with life-stressor checklist scores. 28 In summary, the evidence above suggests hypotheses that depressive disorder underwent chronic negative stress, especially the life stress, may be one potential subtype of MDD, and hippocampus may participate in the the pathogenic process of depression in those who underwent chronic stress. However, there is little research evidence now to support this hypotheses in these patients, and the role of hippocampus is worth further discussion.…”
Section: Introductionmentioning
confidence: 96%
“… 26 , 27 Another study investigated the differences of hippocampal subfield volumes using 7-Tesla MRI, and analyzed the association between life-stressor and hippocampal subfield volumes, found right-hemisphere CA2/3 subfield volume reduced in MDD patients, and left CA1, left CA4/DG, right subiculum total, left hippocampus total, and right hippocampus total were negatively associated with life-stressor checklist scores. 28 …”
Section: Introductionmentioning
confidence: 99%
“…Extensive research in both rodents and humans had indicated its involvement not only in memory processes but also in anxiety (Bannerman et al, 2004 (Satpute et al, 2012). Furthermore, individuals with GAD had been found to exhibit reduced hippocampal volume compared to healthy controls (Alper et al, 2023;Bremner et al, 2000;Gray, Müller, Eickhoff, & Fox, 2020). In contrast to the amygdala's primary role in processing cues that predicted threatening or aversive stimuli, the hippocampus was crucial in processing contextual information related to threat (Alexandra Kredlow, Fenster, Laurent, Ressler, & Phelps, 2022).…”
mentioning
confidence: 99%